Beitrag zur Morphologie und systematischen Stellung von Aleurodes proletella L. (Homoptera: Aleurodidae). - Stein, Ernst (Contributions to Entomology = Beiträge zur Entomologie, 1959)
The morphology of the developmental stages of Aleurodes proletella L. is described. Specimens from Brassica oleracea L. and Chelidonium majus L. cannot be separated by means of their shape. They were also found to agree in selection of host plants. Thus and by fertile cross-breeding the identity of the hitherto separated species A. brassicae Walk. and A. proletella L. is indicated.